2022
DOI: 10.3390/ma15103632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated Temperature on the Residual Behavior of Concrete Containing Marble Dust and Foundry Sand

Abstract: Concrete is a composite material that is commonly used in the construction industry. It will certainly be exposed to fires of varying intensities when used in buildings and industries. The major goal of this article was to look into the influence of mineral additions such as foundry sand and marble dust on the residual characteristics of concrete. To examine the behavior of residual characteristics of concrete after fire exposure, marble dust was substituted for cement and fine sand was substituted for foundry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Production and construction have a point of contact in the form of production of building materials, products, and structures. There are several works devoted primarily to solving environmental and economic problems through the disposal of various types of waste by using them in building materials [3,5,[12][13][14][15][16]19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. In addition, there are works related to the improvement of the properties of composite building materials, products, structures, and first, concretes due to their nano-modification [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Characteristics Of Concretes and Mortarsmentioning
confidence: 99%
“…Production and construction have a point of contact in the form of production of building materials, products, and structures. There are several works devoted primarily to solving environmental and economic problems through the disposal of various types of waste by using them in building materials [3,5,[12][13][14][15][16]19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. In addition, there are works related to the improvement of the properties of composite building materials, products, structures, and first, concretes due to their nano-modification [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Characteristics Of Concretes and Mortarsmentioning
confidence: 99%
“…EDX analyses of concrete with 0% (M1) and 2 % (M6) soap solution are shown in Figure 9 and Figure 10 respectively. From the EDX analysis also, it is found that the concrete with 2% soap solution (M6) showed more silica element formation than the concrete with no soap solution (M1) [ 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nitrile Rubber is the acrylonitrile butadiene rubber that is, obtained from the milling shoe soles and industrial waste blackish in color [ 8 , 30 , 31 ]. Table 3 showcases the properties of NBR as obtained from the vendor.…”
Section: Methodsmentioning
confidence: 99%